Sarcopenia and malnutrition in elderly admitted to hospital - Dias, Ana (2019)
Introduction: Sarcopenia is a progressive and generalized skeletal muscle disorder. The sarcopenia phenotype is also associated with malnutrition, regardless of whether the malnourished condition is rooted in low dietary intake, reduced nutrient bioavailability or high nutrient requirements. Aims: Relating sarcopenia with malnutrition. Materials and Methods: Cross-sectional study, developed at a central hospital, between April and July 2019. Elderly people (≥ 70 years) admitted to internal medicine service with the capacity to make their informed consent, without the intervention of any element of coercion were admitted to the study. Sarcopenia was assessed through the European Working Group on Sarcopenia criteria in Older People (EWGSOP), which include the evaluation of the grip strength (GS), appendicular skeletal muscle mass (ASM) predicted by bioelectrical impedance analysis and physical performance (gait speed). The risk of malnutrition was assessed according to the Mini Nutrition Assessment - MNA® Elderly. Results: n=32 patients, with a mean age of 79.7 + 5.9 years (70-91). At hospital admission 93.8% (n=30) were sarcopenic, 100% (n=30) presented low GS, 75% (n=24) had low ASMM and 3.1% (n=1) had normal gait speed. According to the MNA® short form, 59% (n=19) had a nutritional risk and of that group, 68% (n=13) were at risk of malnutrition and 16% (n=3) were malnourish after completing the MNA® long-form, both also had a diagnostic of sarcopenia. However, there were no significant correlations between the MNA® and the sarcopenia evaluation criteria. Discussion/Conclusion: In a population of geriatric inpatients, subjects with malnutrition risk and sarcopenia are at increased risk of long-term all-cause mortality compared to subjects with either malnutrition/malnutrition risk or sarcopenia. Therefore, the malnutrition-sarcopenia syndrome may serve as an important prognostic factor in the management of hospitalized older patients.